Analisis sensori dan gizi kerupuk sagu kaya nutrisi dari ulat sagu (Rhyinchophorus ferrugineus) - I Putu Suparthana; Adina Juniati Vortina Panggabean; Ni Made Yusa (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Kerupuk is a populist cracker in Indonesia. Its production in this study is aimed to promote kerupuk to become a healthy snack food by utilizing the local protein source namely the larva of Rhynchophorus ferrugineus which is processed into flour. The proportion of Sagu flour and larva flour as the main part of the dough was studied to find the one which resulted in the best product. The experiment was conducted as a Randomized block designed with five level treatments namely the ratio of 100:0; 90:10; 80:20; 70:30; and 60:40. Sensory and nutrient parameters data were analyzed by using analysis of variance tool. The panelists accepted the product resulting from the dough with the ratio of 90 % sagu flour and 10 % larva flour. It contains of 8.72 % of water, 1.65 % of ash, 5.25 % of protein, 0.94 % of fat, 82.20 % of carbohydrates and the swellability is 10.60 %. It was concluded that the 90 %:10 % proportion of sagu flour and larva flour resulted in the best product.